Pemberdayaan Masyarakat melalui Pengembangan Desa Wisata - Apriyani, Sinta; Nugroho, E. W. Tri (Journal Pemberdayaan Masyarakat Indonesia, 2024)
From the development of the Kajigelem Tourism Village, the village government can empower the craftsmen and the community in the Bangunjiwo Village. (1) At the awareness stage, the community is involved in the form of socialization carried out by the village government through the head of the RT/hamlet in Bangunjiwo village, especially the hamlet which has a craft center. (2) At the capacity building stage, the community/tourist actors participate in capacity building by participating in training organized by the government in the form of administrative management training and knowledge of marketing management. (3) At the stage of improving intellectual abilities, the community has been involved in activities in the Kajigelem Tourism Village and some of the handicrafts produced by the community are displayed to attract visiting tourists. The community empowerment process is also constrained by the limited budget owned by the Bangunjiwo Village Government, so that until now the handicrafts have not been widely displayed in the Kajigelem Tourism Village.